The Role of Female Ulama in Formulating Eco-Friendly Fatwas: A Case Study in Indonesia - Asnal Mala; Ali, Elli Masnawati; Masfufah (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
This study examines the role of female scholars in formulating environmentally friendly fatwas in Indonesia, highlighting how gender perspectives influence religious approaches to ecological issues. This research is important because it highlights the contributions of female scholars from highly patriarchal communities, showing how they can articulate environmental issues as a religious mandate and provide faith-based responses to the ecological crisis—an approach that is rarely found in mainstream fatwas. This study used a qualitative approach with a case study method. Data were collected through in-depth interviews with 12 female scholars involved in drafting environmental fatwas in East Java, West Nusa Tenggara, and South Sulawesi, supplemented by fatwa document analysis and participatory observation in regional religious forums. Data were analyzed using qualitative content analysis, focusing on gender narratives, ecological theological frameworks, and argument patterns in fatwas. The findings show that female scholars play a strategic role in promoting sustainable environmental practices on religious platforms. These findings emphasize that gender is not merely a social variable but a crucial factor in religious leadership and the use of fatwas as an effective tool for ecological advocacy in Muslim communities. [Tujuan penelitian ini mengkaji peran ulama perempuan dalam merumuskan fatwa ramah lingkungan di Indonesia, dengan menyoroti bagaimana perspektif gender memengaruhi pendekatan agama terhadap isu-isu ekologis. Penelitian ini signifikan karena menyoroti kontribusi ulama perempuan dari komunitas yang sangat patriarkis, menunjukkan bagaimana mereka mampu memposisikan isu lingkungan sebagai amanah keagamaan dan memberikan respons keagamaan terhadap krisis ekologis, yang jarang terlihat dalam fatwa mainstream. Penelitian menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui wawancara mendalam dengan 12 ulama perempuan yang terlibat dalam perumusan fatwa lingkungan di Jawa Timur, Nusa Tenggara Barat, dan Sulawesi Selatan, dilengkapi dengan analisis dokumen fatwa dan observasi partisipatif pada forum keagamaan regional. Data dianalisis menggunakan analisis isi kualitatif, dengan fokus pada narasi gender, kerangka ekoteologis, dan pola argumentasi dalam fatwa.Hasil penelitian menunjukkan bahwa ulama perempuan memainkan peran strategis dalam mendorong praktik lingkungan berkelanjutan melalui platform keagamaan. Temuan ini menegaskan bahwa gender bukan sekadar variabel sosial, melainkan faktor penting dalam kepemimpinan agama dan penggunaan fatwa sebagai instrumen advokasi ekologis yang efektif di masyarakat Muslim].